IMPACT OF CLIMATE CHANGE ON MILLET YIELD IN INDIA SINCE 1991: AN ECONOMETRIC ANALYSIS - KRISHNA KUMAR JADAUN*; AKRAM AHMAD KHAN (The Journal of Research ANGRAU, 2023)
This study examines the effects of climate change on millet yield in India using secondary data for thirty years (1991-2020). The variation in agricultural millet production in India is estimated using average annual temperature, precipitation, CO2 emissions per capita, and the rural population. Assessing the order of integration using the unit root test and augmented DickeyFuller (ADF). Estimations of the unit root demonstrate that all variables are stationary at the level and first difference. The autoregressive distributive lag (ARDL) bound test is applied to establish the relationship between variables. The study demonstrates that the average yearly temperature has a negative and significant effect on millet yield, whereas, CO2 emission per capita has a favourable long-term impact on millet yield. In India, 1% increase in yearly average temperature results in a 3.06% decrease in millet yield, while 1% increase in CO2 emissions per capita results in a 0.42% gain in millet yield on average. In the short run, independent variables do not affect millet yield. As the population of India grows, the nation will face food security issues. There is a need for strategies to mitigate the negative impact of temperature on agricultural yield and secure sufficient food for a growing population